Transformasi SDM UMKM melalui Digitalisasi Produksi: Studi Kasus ZAFA SNACK Kudus - Endang Supriyati; Tri Listyorini; Mohammad Iqbal (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service study examines the human resource (HR) capacity transformation at UMKM Zafa Snack Kudus as an outcome of appropriate technology training. Drawing on a digital literacy framework and andragogical approach, the intervention was designed to build sustainable technological independence. Two primary instruments were deployed: a 4–6 kg electric dehydrator and a cloud-based Google Sheets production recording system. The community service program was implemented through a participatory approach consisting of socialization, training, technology implementation, mentoring, and program evaluation. Results indicate that HR transformation occurred in three progressive phases: resistance, adaptation, and internalization. A 70–80% improvement in drying time efficiency was a technical outcome, but the more substantial outcome was the emergence of data literacy among business actors, subsequently driving more rational and standardized production decision-making. This program reinforces the argument that successful technology adoption in MSMEs is not solely determined by equipment availability, but by the readiness and capacity of its human resources.